Kolaborasi Mengajar antara Universitas dan Sekolah - Pandu Adi Cakranegara; Johan Krisnanton Runtuk; Ika Widiastuti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Lecturers at the university and having an obligation to teach students and conduct research should also do community service. One of the communities that need to be assisted by the university is the community around the university. Therefore, this community service is intended to help elementary schools located within the university environment in dealing with the Covid 19 Pandemic. Online learning poses a challenge because it is not easy to transfer face-to-face learning to online learning. In this service, lecturers collaborate with teachers to design online education. In addition, the lecturer team also donated credits to help students in need. The result of this service is that elementary school students can continue to follow online learning without experiencing material lag. The lecturer team can look for collaboration opportunities with various institutions around the university in the future.